Long-term effect on the immune status of defined diets during the early postnatal period in the rat - Stĕpánková, R; Sterzl, J; Trebichavský, I (Physiologia Bohemoslovaca, 1985)
Germ-free and conventional infant rats delivered by hysterectomy were reared artificially, using one of two diets--diet LNa (with a high saturated fatty acid content) and diet K 50 (with a high unsaturated fatty acid content). Animals reared for a short time (up to 5 days) after birth on the LNa diet had a low antibody (PFC = plaque-forming lymphocyte) response and low resistance to Yoshida's sarcoma. Rats reared on the K 50 diet had the same response as the suckled controls. The first 5 days after birth were found to be the decisive period for long-term consequences of nutrition.
Keywords: nenasycené mastné kyseliny; inbrední kmeny potkanů; Rats, Inbred Strains; Rats; Animals, Newborn; Dietary Fats; tvorba protilátek; Sarcoma; Neoplasm Transplantation; Time Factors; buněčné dělení; Fatty Acids; mužské pohlaví; dietní tuky; Cell Division; novorozená zvířata; Antibody Formation; krysa rodu Rattus; ženské pohlaví; zvířata; transplantace nádorů; sarkom; časové faktory; mastné kyseliny; Fatty Acids, Unsaturated; Female; Male; Animals